Operative and Survival Outcomes of Robotic-Assisted Surgery for Colorectal Cancer in Elderly and Very Elderly Patients: A Study in a Tertiary Hospital in South Korea. (30th January 2022) - Cuellar-Gomez, Hugo; Rusli, Siti Mayuha; Ocharan-Hernández, María Esther; Lee, Tae-Hoon; Piozzi, Guglielmo Niccolò; Kim, Seon-Hahn; Vargas-De-León, Cruz
Abstract : Introduction and Objectives . Most patients with colorectal cancer are elderly. Literature is scarce on elderly patients submitted to robotic-assisted surgery, despite the feasibility shown in other age groups. The aim of this study was to evaluate the postoperative and survival outcomes of robotic-assisted colorectal cancer surgery in elderly patients. Materials and Methods . Data of all patients ≥75 years who underwent a robotic-assisted curative resection in Korea University Anam Hospital, Seoul, South Korea, between January 2007 and January 2021 were extracted from a prospectively maintained colorectal cancer database. Patients were subdivided into the three groups according to the age: youngest-old (YO: 75–80 years), middle-old (MO: 81–85), and oldest-old (OO: ≥86 years). Intraoperative findings, postoperative, and oncological outcomes were compared between the groups. Results . Seventy-six consecutive patients (female 52.6%) were included; mean age was 80 years (SD 0.33); mean body mass index (BMI), 23.8 20.9 kg/m 2 (SD 3.58); mean total operative time, 279 min (SD 80.93); mean blood loss, 186 ml (SD 204.03); mean postoperative length of stay, 14 days (SD 12.03). Major complications were seen in 2.1% of patients. The 30-day mortality rate was 0%. Average number of lymph node harvested was 20.9 (SD 12.33). Postoperative complications were not statistically different between the groups. Mean follow-up time for cancer-specific survival (CSS) was 99.28 months for the YO, 72.11 months for MO, and 31.25 months for OO groups (p  = 0.045). The CSS rates at 5 years were 27.0%, 21.0%, and 0%, respectively. Recurrence risk was 10.50 times higher in the OO group than the others (adjusted HR, 95% CI 1.868–59.047, p  = 0.008). In the multivariable analysis, TNM stage was not a risk factor for CSS in all groups. The number of the harvested nodes was a protective factor for recurrence (HR of 0.932, 95% CI 0.875–0.992, p  = 0.027) and CSS (HR of 0.928, 95% CI 0.861–0.999, p  = 0.047) in elderly patients. Conclusion . Robotic surgery is highly feasible in elderly and very elderly colorectal cancer patients, providing a favorable operative safety profile and an acceptable cancer-specific survival outcome.